Cognitive science: an interdisciplinary approach - "Sobel, Carolyn P." (New Delhi, 2013)
This engagingly written introduction to the cognitive sciences examines the historical and contemporary issues, and research findings of the core cognitive science disciplines, including cognitive psychology, neuroscience, language, philosophy, and artificial intelligence. For each of the core disciplines of cognitive science, the historical development and classic research studies are presented in one chapter and current research development and issues follow in a second chapter. The student is given insight into the way each discipline has contributed to the growth of cognitive science and what directions research is taking in the future. This text assumes no background on the part of the reader.
Keywords: Cogniative science